Penyimpangan HAM Menuju Politik Identitas - Pattiserlihun, Selvone Christin (Satya Widya: Jurnal Studi Agama, 2024)
Human rights violations against women and children in Indonesia's Freedom of Religion and Belief (FoRB) are visible in public spaces. This article focuses on cases that often occur in multicultural societies. This article aims to identify, discuss, and comment on human rights violations in the religious form prohibitions and coercion in public schools, which impact the development of identity politics in Indonesia. The method used is a qualitative multiple-case study that will discuss and compare several cases of human rights violations in children's religious clothing in public schools using online media and a review of regulatory literature as a data source. The results of this research show four findings namely first, forced use of religious clothing occurs in Muslim-majority areas. Meanwhile, the prohibition on wearing religious clothing occurs in non-Muslim majority areas. Second, religious legislation for educational institutions in certain areas is still based on the most relevant religious regions. Third, the contest of burning clothing has an impact on the victim's psychological, physical, and relational disorders. Fourth, cultural contestation is a means of perpetuating identity politics and targeting vulnerable groups such as women and children. Thus, the state has a big task to guarantee religious freedom in vulnerable spaces.